I know this much is true [videorecording (DVD)] - Cianfrance, Derek; Ruffalo, Mark; Leo, Melissa; Panjabi, Archie; O'Donnell, Rosie (Warner Home Video, 2021)
A tour-de-force performance from Mark Ruffalo leads this family saga, which follows the parallel lives of identical twin brothers in an epic story of betrayal, sacrifice and forgiveness set against the backdrop of 20th-century America. The six-episode limited drama series is based on Wally Lamb's New York Times bestseller and award-winning book, I Know This Much Is True.